Multiple drug combinations of bortezomib, lenalidomide, and thalidomide for first‐line treatment in adults with transplant‐ineligible multiple myeloma: a network meta‐analysis - Piechotta, Vanessa (Cochrane Database Syst Rev, 2019)
BACKGROUND: Multiple myeloma is a bone marrow‐based hematological malignancy accounting for approximately two per cent of cancers. First‐line treatment for transplant‐ineligible individuals consists of multiple drug combinations of bortezomib (V), lenalidomide (R), or thalidomide (T). However, access to these medicines is restricted in many countries worldwide. OBJECTIVES: To assess and compare the effectiveness and safety of multiple drug combinations of V, R, and T for adults with newly diagnosed transplant‐ineligible multiple myeloma and to inform an application for the inclusion of these medicines into the World Health Organization's (WHO) list of essential medicines. SEARCH METHODS: We searched CENTRAL and MEDLINE, conference proceedings and study registries on 14 February 2019 for randomised controlled trials (RCTs) comparing multiple drug combinations of V, R and T for adults with newly diagnosed transplant‐ineligible multiple myeloma. SELECTION CRITERIA: We included RCTs comparing combination therapies of V, R, and T, plus melphalan and prednisone (MP) or dexamethasone (D) for first‐line treatment of adults with transplant‐ineligible multiple myeloma. We excluded trials including adults with relapsed or refractory disease, trials comparing drug therapies to other types of therapy and trials including second‐generation novel agents. DATA COLLECTION AND ANALYSIS: Two review authors independently extracted data and assessed risk of bias of included trials. As effect measures we used hazard ratios (HRs) for overall survival (OS) and progression‐free survival (PFS) and risk ratios (RRs) for adverse events. An HR or RR < 1 indicates an advantage for the intervention compared to the main comparator MP. Where available, we extracted quality of life (QoL) data (scores of standardised questionnaires). Results quoted are from network meta‐analysis (NMA) unless stated. MAIN RESULTS: We included 25 studies (148 references) comprising 11,403 participants and 21 treatment regimens. Treatments were differentiated between restricted treatment duration (treatment with a pre‐specified amount of cycles) and continuous therapy (treatment administered until disease progression, the person becomes intolerant to the drug, or treatment given for a prolonged period). Continuous therapies are indicated with a "c". Risk of bias was generally high across studies due to the open‐label study design. Overall survival (OS) Evidence suggests that treatment with RD (HR 0.63 (95% confidence interval (CI) 0.40 to 0.99), median OS 55.2 months (35.2 to 87.0)); TMP (HR 0.75 (95% CI 0.58 to 0.97), median OS: 46.4 months (35.9 to 60.0)); and VRDc (HR 0.49 (95% CI 0.26 to 0.92), median OS 71.0 months (37.8 to 133.8)) probably increases survival compared to median reported OS of 34.8 months with MP (moderate certainty). Treatment with VMP may result in a large increase in OS, compared to MP (HR 0.70 (95% CI 0.45 to 1.07), median OS 49.7 months (32.5 to 77.3)), low certainty). Progression‐free survival (PFS) Treatment withRD (HR 0.65 (95% CI0.44 to 0.96), median PFS: 24.9 months (16.9 to 36.8)); TMP (HR 0.63 (95% CI 0.50 to 0.78), median PFS:25.7 months (20.8 to 32.4)); VMP (HR 0.56 (95% CI 0.35 to 0.90), median PFS: 28.9 months (18.0 to 46.3)); and VRDc (HR 0.34 (95% CI 0.20 to 0.58), median PFS: 47.6 months (27.9 to 81.0)) may result in a large increase in PFS (low certainty) compared to MP (median reported PFS: 16.2 months). Adverse events The risk of polyneuropathies may be lower with RD compared to treatment with MP (RR 0.57 (95% CI 0.16 to 1.99), risk for RD: 0.5% (0.1 to 1.8), mean reported risk for MP: 0.9% (10 of 1074 patients affected), low certainty). However, the CIs are also compatible with no difference or an increase in neuropathies. Treatment with TMP (RR 4.44 (95% CI1.77 to 11.11), risk: 4.0% (1.6 to 10.0)) and VMP (RR 88.22 (95% CI 5.36 to 1451.11), risk: 79.4% (4.8 to 1306.0)) probably results in a large increase in polyneuropathies compared to MP (moderate certainty). No study reported the amount of participants with grade ≥ 3 polyneuropathies for treatment with VRDc. VMP probably increases the proportion of participants with serious adverse events (SAEs) compared to MP (RR 1.28 (95% CI 1.06 to 1.54), risk for VMP: 46.2% (38.3 to 55.6), mean risk for MP: 36.1% (177 of 490 patients affected), moderate certainty). RD, TMP, and VRDc were not connected to MP in the network and the risk of SAEs could not be compared. Treatment with RD (RR 4.18 (95% CI 2.13 to 8.20), NMA‐risk: 38.5% (19.6 to 75.4)); and TMP (RR 4.10 (95% CI 2.40 to 7.01), risk: 37.7% (22.1 to 64.5)) results in a large increase of withdrawals from the trial due to adverse events (high certainty) compared to MP (mean reported risk: 9.2% (77 of 837 patients withdrew)). The risk is probably slightly increased with VMP (RR 1.06 (95% CI 0.63 to 1.81), risk: 9.75% (5.8 to 16.7), moderate certainty), while it is much increased with VRDc (RR 8.92 (95% CI 3.82 to 20.84), risk: 82.1% (35.1 to 191.7), high certainty) compared to MP. Quality of life QoL was reported in four studies for seven different treatment regimens (MP, MPc, RD, RMP, RMPc, TMP, TMPc) and was measured with four different tools. Assessment and reporting differed between studies and could not be meta‐analysed. However, all studies reported an improvement of QoL after initiation of anti‐myeloma treatment for all assessed treatment regimens. AUTHORS' CONCLUSIONS: Based on our four pre‐selected comparisons of interest, continuous treatment with VRD had the largest survival benefit compared with MP, while RD and TMP also probably considerably increase survival. However, treatment combinations of V, R, and T also substantially increase the incidence of AEs, and lead to a higher risk of treatment discontinuation. Their effectiveness and safety profiles may best be analysed in further randomised head‐to‐head trials. Further trials should focus on consistent reporting of safety outcomes and should use a standardised instrument to evaluate QoL to ensure comparability of treatment‐combinations.